Assessing the quality of transmission of lightpaths in multiband C+L networks through Gaussian noise models - Venda, P.; Rebola, J.; Cancela, L. (Optical Fiber Technology, 2022)
In an optical network scenario, wavelength division-multiplexing (WDM) channels are constantly being added and dropped, leading to dynamic traffic variations in the lightpaths. In this work, the impact of the network traffic load and spectral occupancy on the quality of transmission, namely on the normalized nonlinear interference (NLI) power, power transfer due to stimulated Raman scattering (SRS) and optical signal-to-noise ratio (OSNR) of the lightpaths in a C+L multiband optical network is assessed using the recently proposed closed-form interchannel SRS Gaussian noise model (ISRS GN-model). We show that, due to the dynamic traffic behavior, the normalized NLI power can oscillate up to 2 dB in the highest frequency channels due to NLI variations when the tested channels have unequal spacing along the spectrum. For the optimum channel launch power and by increasing the network traffic load, the power transfer between the outer channels can increase up to 5.1 dB due to the SRS effect. With 201 WDM channels, high traffic load and for the optimum channel power, we obtained a maximum OSNR variation along the channel frequencies of only about 0.7 dB. A comparison between the OSNR predictions of the closed-form ISRS GN-model and a closed-form Gaussian noise (GN) model that does not take into account the SRS effect is also performed. In all results obtained, the maximum difference between the OSNR predictions of GN (without SRS) and ISRS GN models is below 0.7 dB at optimum OSNR and maximum C+L band occupancy. For channel launch powers higher than the optimum, the OSNR differences increase up to 3 dB.